2021
DOI: 10.1002/jclp.23269
|View full text |Cite
|
Sign up to set email alerts
|

Minnesota Multiphasic Personality Inventory‐Adolescent‐Restructured Form (MMPI‐A‐RF) characteristics of ADHD in a Korean psychiatric sample

Abstract: Global rates of attention-deficit/hyperactivity disorder (ADHD) have risen. In Korea, ADHD is associated with functional impairments and comorbidity with other psychological disorders. This study examined the correlates of ADHD in a psychiatric sample of Korean adolescents on the Minnesota Multiphasic Personality Inventory-Adolescent-Restructured Form (MMPI-A-RF). In a clinical sample of 247 adolescents, MMPI-A-RF scores from 46 patients diagnosed with ADHD were compared to the remainder of the clinical sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Regarding the scales associated with externalizing disorder, our study showed higher scores on the Externalizing Scales (CNP and NPI) in the externalizing group. Among the five main domains, the externalizing problem is related to the Behavioral Dysfunction domain of the MMPI-A-RF [ 22 ]. Furthermore, in a recent MMPI-A-RF study on ADHD, which is the most typical externalizing disorder, an ADHD group reported significantly different scores on scales indicating externalizing concerns and behavioral dysfunction compared with a non-ADHD group [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the scales associated with externalizing disorder, our study showed higher scores on the Externalizing Scales (CNP and NPI) in the externalizing group. Among the five main domains, the externalizing problem is related to the Behavioral Dysfunction domain of the MMPI-A-RF [ 22 ]. Furthermore, in a recent MMPI-A-RF study on ADHD, which is the most typical externalizing disorder, an ADHD group reported significantly different scores on scales indicating externalizing concerns and behavioral dysfunction compared with a non-ADHD group [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the five main domains, the externalizing problem is related to the Behavioral Dysfunction domain of the MMPI-A-RF [ 22 ]. Furthermore, in a recent MMPI-A-RF study on ADHD, which is the most typical externalizing disorder, an ADHD group reported significantly different scores on scales indicating externalizing concerns and behavioral dysfunction compared with a non-ADHD group [ 22 ]. The findings of the present study, which showed significantly higher CNP and NPI scores in the externalizing disorder group, are consistent with those of Chakranarayan et al [ 22 ], demonstrating that the BXD, RC4, CNP, NPI, and DISC-r scales have diagnostic relevance for ADHD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation